2010
DOI: 10.1074/jbc.m110.127183
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Synthesis Mediates the Fibrotic Response of Keratocytes to Transforming Growth Factor β

Abstract: TGF␤ induces fibrosis in healing corneal wounds, and in vitro corneal keratocytes up-regulate expression of several fibrosisrelated genes in response to TGF␤. Hyaluronan (HA) accumulates in healing corneas, and HA synthesis is induced by TGF␤ by up-regulation of HA synthase 2. This study tested the hypothesis that HA acts as an extracellular messenger, enhancing specific fibrotic responses of keratocytes to TGF␤. HA synthesis inhibitor 4-methylumbelliferone (4MU) blocked TGF␤ induction of HA synthesis in a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 25 publications
(42 reference statements)
0
25
0
1
Order By: Relevance
“…Although the role of HA in wound healing has been clarified with various research (David-Raoudi et al 2008;Guo et al 2010;Larson et al 2010), the specialized role of HAS-1, HAS-2 and HAS-3 has not yet been elucidated. HA accumulation during wound healing process is known to be induced by TGF-b1 which facilitates up-regulation of HAS-2 (Guo et al 2010).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the role of HA in wound healing has been clarified with various research (David-Raoudi et al 2008;Guo et al 2010;Larson et al 2010), the specialized role of HAS-1, HAS-2 and HAS-3 has not yet been elucidated. HA accumulation during wound healing process is known to be induced by TGF-b1 which facilitates up-regulation of HAS-2 (Guo et al 2010).…”
Section: Discussionmentioning
confidence: 98%
“…HA accumulation during wound healing process is known to be induced by TGF-b1 which facilitates up-regulation of HAS-2 (Guo et al 2010). It has been known for a long time that HA is abundant in the early granulation tissue of dermal wounds, and associates with scar-less healing (Larson et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Vivo-We used 4MU, a well established and specific inhibitor of hyaluronan production (3,7,(13)(14)(15)(16)(17)20), to modulate hyaluronan synthesis. First, we confirmed the inhibitory influence of 4MU on hyaluronan synthesis by in vitro experiments.…”
Section: Mu Feeding Inhibits Hyaluronan Production In Vitro and Inmentioning
confidence: 99%
“…In the present study, we assessed the effect of hyaluronan in EAE by inhibiting hyaluronan synthesis with 4-methylumbelliferone (4MU) administration (3,(13)(14)(15)(16)(17). 4MU inhibits hyaluronan synthesis in a dose-dependent manner by two mechanisms: depletion of cellular UDP-glucuronic acid and down-regulation of hyaluronan synthases 2 and 3 (14).…”
mentioning
confidence: 99%
“…KS is also implicated in corneal wound repair. 4,5 As corneal microsurgery is advancing into the myriad of refractive surgery options for myopia, hyperopia, presbyopia and astigmatism and transplantation procedures, both fullthickness and lamellar, the concept of the role of GAG in wound healing is becoming even more important. It has been observed that the total amount of GAG increases by 30-40% in corneas of older population and hence corneal surgeries have to be planned keeping in mind the difference in wound healing and post-operative regeneration across the ages.…”
mentioning
confidence: 99%